Total Synthesis and Stereochemical Reassignment of Mandelalide A. Issue 25 (18th May 2014) - Lei, Honghui; Yan, Jialei; Yu, Jie; Liu, Yuqing; Wang, Zhuo; Xu, Zhengshuang; Ye, Tao
Abstract: The total synthesis of the tunicate metabolite mandelalide A and the correction of its originally assigned stereochemistry are reported. Key features of the convergent, fully stereocontrolled route include the use of a Prins cyclization for the diastereoselective construction of the tetrahydropyran subunit, Rychnovsky–Bartlett cyclization for the preparation of the tetrahydrofuran moiety, Suzuki coupling, Horner–Wadsworth–Emmons macrocyclization, and glycosylation to append the L ‐rhamnose‐derived pyranoside. Abstract : Structural revision : A revised configurational assignment for the marine macrolide mandelalide A is proposed and validated by total synthesis. This study is one of several recent examples in a growing list of investigations that correct misassigned structures of natural products by stereocontrolled total synthesis.